2015
DOI: 10.1016/j.echo.2015.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Libman-Sacks Endocarditis: Detection, Characterization, and Clinical Correlates by Three-Dimensional Transesophageal Echocardiography

Abstract: Background Libman-Sacks endocarditis, characterized by Libman-Sacks vegetations, is common in patients with systemic lupus erythematosus (SLE), and is commonly complicated with embolic cerebrovascular disease. Thus, accurate detection of Libman-Sacks vegetations may lead to early therapy and prevention of their associated complications. Although two-dimensional transesophageal echocardiography (2D-TEE) has high diagnostic value for detection of Libman-Sacks vegetations, three-dimensional TEE (3D-TEE) may allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 30 publications
(57 reference statements)
3
53
0
7
Order By: Relevance
“…The mean size of atrial thrombus caused by typical LSE is reported to be 3.9 ± 1.3 mm, with a maximum size of 10 mm, which is smaller than what was seen in our patient (29 mm). 14 Typical LSE sometimes involves not only one small thrombus but also multiple small thrombi. On the other hand, this patient had only one large thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…The mean size of atrial thrombus caused by typical LSE is reported to be 3.9 ± 1.3 mm, with a maximum size of 10 mm, which is smaller than what was seen in our patient (29 mm). 14 Typical LSE sometimes involves not only one small thrombus but also multiple small thrombi. On the other hand, this patient had only one large thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…It is detected in 43 % of patients with SLE using transesophageal echocardiography (TEE). 4 Three-dimensional TEE may have an additive and complementary value in the detection of LS endocarditis, 6 which most commonly involves the mitral valve, followed by the aortic valve. 7 LS endocarditis has been reported to be associated with higher disease activity, longer disease duration, and positive anticardiolipin and antiphospholipid antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to the highly mobile, narrow-based infectious vegetations that tend to be homogeneous in echogenicity and associated with a variable degree of valvular insufficiency and perforation. 4,6 The modified Duke criteria are sensitive for the diagnosis of infectious endocarditis. However, these criteria do not help in distinguishing infective from non-infective endocarditis, as multiple criteria are shared by these two conditions.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve the highest spatial and temporal resolution, we obtained electrocardiographically triggered multiple-beat (4 beats) high-density full volume images with the narrowest possible sector scan during breath-holding (expiration). (10) Contrast echocardiography(11) was conducted following 2D-echocardiography in gray-scale ultraharmonic mode. Mean transmitting frequency and receiving frequency were 1.3 and 3.6 MHz, respectively.…”
Section: Transesophageal Echocardiographymentioning
confidence: 99%